Systematic Literature Review: Exploring the Impact of Contemporary Diets on Long-Term Health - Eridani Khairunnisa; Sri Widati; Oedojo Soedirham (Riviera Publishing, 2025)
This systematic literature review investigates the long-term health effects of contemporary diets, focusing on low-carb, ketogenic, intermittent fasting, and plant-based diets. The review analyzes studies published from 2015 to 2025, with an emphasis on their impacts on cardiovascular health, metabolic disorders, obesity, and overall quality of life. The results indicate that while ketogenic and low-carb diets are effective in weight loss and managing metabolic health, concerns regarding long-term sustainability and potential risks, such as nutrient deficiencies and cardiovascular implications, need to be addressed. Intermittent fasting shows promising results in improving metabolic health and longevity but poses challenges related to adherence. Plant-based diets were associated with reduced risks of chronic diseases, though potential nutrient deficiencies require careful management. The review concludes that no single diet fits all; personalized nutrition based on individual needs, health conditions, and lifestyle is key to achieving long-term health benefits. Further research is needed to determine the optimal approaches for maintaining health through diet over extended periods.